Recurrence and Management Challenges of Upper Eyelid Pilomatrixoma: A Rare Case Study with Atypical Presentation - Mohammad , Najah K. (AL-Kindy College Medical Journal, 2025)
Pilomatrixoma is a benign tumor of the hair matrix cells and is usually confused with other entities since there are nonspecific findings. Most of the patients are young individuals, and involvement is usually in the head and neck region; however, rarely, involvement in the periorbital area has been reported. We present the recurrent case of pilomatrixoma in a 37-year-old male upper eyelid, as well as diagnostic and treatment difficulties that are commonly found in these tumors. The tumor was initially excised under local anesthesia. After three months, it recurred, which was further confirmed on histopathology as pilomatrixoma due to its characteristic features of basaloid cells and ghost cell formation. A good point here is that a recurrent tumor following good initial removal points to the necessity for very careful follow-up or, perhaps, more aggressive initial surgery. This underlines the fact that pilomatrixoma can present with a varied clinical spectrum; hence, histopathological confirmation is necessary for case definition. Pilomatrixoma, in some way, recalls the fact that, though the treatment is adequate at first, a chance of recurrence is probable and, thus, contributes to the body of experience in managing this rare disease.